Application of GIS-planning decision support system in predicting development impact assessment - Asmawi, M. Zainora; Abdullah, Muhammad Faris; Abdullah, Alias; Shahbudin, Muhamad Nur Azraei (International Society for Photogrammetry and Remote Sensing, 2011)
Impact of development is a major issue of global environment change. The modelling and projecting of development are essential to the assessment of consequent environmental impacts. Thus, this research was conducted to develop a customised modelling system that integrates the strength of GIS in supporting planning decision making process via prediction of development impact assessment for various projects. It is in this respect that a prototype of GIS-based modelling that enables to anticipate development environmental impacts at an early stage of project planning has been established. It encompasses some selected key components of environment, economy and social, building up the system called e-Development Impact Assessment (e-DIA). The design principle was to extend the functionality of a GIS system in facilitating planning decision support making process. An integrated subsystem of e-DIA allows the analysis of environmental, social and economic dimensions to generate the results of impacts of proposed development in the form of spatial and textual data. In terms of environmental impact assessment, e-DIA acts as a screening/scoping utility which may indicate the potential impacts of a set of pre-determined environmental impacts. For social and economic impact assessments, the e-DIA computes the outcome of future demand for social facilities, future employment opportunity and parking requirement.